HBHA induces IL-10 from CD4+ T cells in patients with active tuberculosis but IFN-γ and IL-17 from individuals with Mycobacterium tuberculosis infection - Izumida, Mai; Jobe, Haddijatou; Coker, Edward G.; Barry, Amadou; Rashid, Momodou; Manneh, Ismaila L.; Daffeh, Georgetta K.; Ariyoshi, Koya; Sutherland, Jayne S. (Frontiers in Immunology, 2024)
Background: To effectively control tuberculosis (TB), it is crucial to distinguish between active TB disease and latent TB infection (LTBI) to provide appropriate treatment. However, no such tests are currently available. Immune responses associated with TB and LTBI are dynamic and exhibit distinct patterns. Comparing these differences is crucial for developing new diagnostic methods and understanding the etiology of TB. This study aimed to investigate the relationship between pro-and anti-inflammatory CD4+ cytokine production following stimulation with two types of latencyassociated Mycobacterium tuberculosis (M.tb) antigens to allow differentiation between TB and LTBI.Methods: Cryopreserved PBMCs from patients with active TB or LTBI were stimulated overnight with replication-related antigen (ESAT-6/CFP-10 (E/C)) or two latency-associated antigens,HBHA and Acr. Responses were analyzed using multiparameter flow cytometry: TB (n=15), LTBI (n=15) and ELISA: TB (n=26) or LTBI (n=27).Results: CD4+ central memory T cells specific to E/C and CD4+ effector memory T cells specific to Acr and HBHA were higher in LTBI than in TB patients. IFN-γ+Tcm and IL-17+ Tem cells was higher in the LTBI group (p= 0.012 and p=0.029 respectively), but IL-10+ Tcm was higher in the TB group (p= 0.029) following HBHA stimulation. Additionally, following stimulation with HBHA, IL-10 production from CD4+ T cells was significantly elevated in patients with TB compared to those with LTBI (p= 0.0038), while CD4+ T cell production of IL-17 and IFN-γ was significantly elevated in LTBI compared to TB (p= 0.0076, p< 0.0001, respectively). HBHA also induced more CCR6+IL-17+CD4Tcells and IL-17+FoxP3+CD25+CD4Tcells in LTBI than in TB patients (P=0.026 and P=0.04, respectively). HBHA also induced higher levels of IFN-γ+IL-10+CD4+ T cells in patients with TB (P=0.03) and higher levels of IFN-γ+IL-17+ CD4+ T cells in those with LTBI (p=0.04). HBHA-specific cytokine production measured using ELISA showed higher levels of IFN-γ in participants with LTBI (P=0.004) and higher levels of IL-10 in those with TB (P=0.04).Stimulation with HBHA and measurement of CD4+ T cell production of IFN-γ, IL-10, and IL-17 could potentially differentiate TB from LTBI. The characteristics of cytokineexpressing cells induced by HBHA also differed between participants with TB and LTBI.